Science Process Skills Test Instruments in The New Indonesian Curriculum (Merdeka): Physics Subject in Renewable Energy Topic - Susilowati, Nisfullail Indah; Liliawati, Winny; Rusdiana, Dadi (Universitas Pendidikan Indonesia (UPI), 2023)
The physics subject in the Merdeka Curriculum is organized into two categories, understanding physics and process skills. The physics process skills assessment instruments used by teachers in the field are not appropriate in terms of assessment methods and the assessment tends to be subjective. This study aims to develop a science process skills test instrument in physics learning for high school students, on the topic of Renewable Energy. The method used in this research is development research. The instrument was developed with the Extended Written Response method, essay-type questions consisting of fifteen written test items. Indicators of science process skills developed are observing, questioning and predicting, planning and conducting investigations, processing, analyzing data and information, creating, evaluating and reflecting, and communicating. The stages of developing this test instrument are making indicators of questions, making questions, judgments by topic experts and assessment experts, revising questions, testing, revising questions, and implementing questions at school. The results showed that the test instrument developed was suitable for use as a process skills test instrument on the Renewable Energy topic.